New Settlement Areas at Forbiden Zone of Merapi Volcano (Case at Srumbung, Magelang) - Ritohardoyo, Su (Forum Geografi, 2000)
One of the chronicle problem in the disaster control of volcano eruption is the resettlement of relocated or transmigrated people to prohibitive region of the volcano. The more serious problem is happened when some of the labourers sand and stone mining living in those prohibitive region. Starting from those stated sttlement problem, this research aims at exposing the change, process, and continuity of setlement in the prohibitive region. This study employs so called sampling technique. Quota sampling is carried out according to village type. Two agricultural and mining village types in the prohibitive region are selected representing the sampling areas, encompassed administrative divisions of Srumbung subdistrict. The number of respondents are 60 households, selected unproportionally based on the village type. Primary data is collected diret communication with informants are key persons. Data analysis employs frequenccy and cross tabulation, and t test analysis. The study reveals that settlement changes in prohibitive region of Merapi vulcano has been fluctuatively recorded since 1006 based on the strength of Merapi vulcano eruption. However intensively settlement changes as an impact of the Merapi vulcano eruption have been recorded sine 1930 up to 1975 followed by more than 1742 people be dead as a victims and environment deterioration. The eruptions in 1954 and 1969 have resulted in drastically changes of physical and administrative condition village of Kaligesik and Gimal. At least 9 hamlets in both villages have been destroyed by ânue ardenteâ and cold lava. Those eruptions have than change the administrative status of villages to be. Resettlement process within two hamlets in prohibitive region have taken place due to differences in origin area of the shelter, motivation to settle, and settlement pattern. Those two settle in mining villages are mining are mining labourer and mostly comes from outer subdistricts or districts, whereas those who stay in agriculture village are local people. The latter mostly joined transmigration program, which are supposed to stay in outer islands. A part from origin area, the difference of two settlers is also indicated by motivation. Economic motives are more dominant for those who settle in mining village than those who settle in agriculture village. The latter tend to have social motives to stay. The difference in settlement pattern between the vilages lays in âintermediary settlementâ. This means that mining settlers have previously stayed in transmigration area. The duration to stay is between 15 to 20 years as compared toÂ mining settlers whose duration to stay are between 5 to 10 years. Although the average household monthly inomeÂ in the respective two vilages is relatif the same (i.e. Rp 323,366 in Kaligesik and Rp 335,557 in Sumberejo), the physical condition of housing in Sumberejo look a little better than in Kaligesik. Despite the respective differences, people in the two villages tend to stay permanently. This means that the effort to vacant these prohibitive region will become more difficult.